Navigating ontological (in) security in EU-Africa relations - Mah, L.; Haastrup, Toni; Duggan, Nial (Global Affairs, 2021)
Six decades on and several attempts to re-set EU-Africa relations, it is appropriate to take stock of the relationship especially in light of changes in both continents since 2000. This article draws on the idea of ontological security to understand the nature of changes and continuities in the EU's engagement with Africa. It argues that EU-Africa relations that have relied on a coloniality of power have also been crucial to the EU's ontological security. However, increasing African agency and new external actors like China in Africa are challenging this security. While challenges to the EU's ontological security have been viewed as primarily internally constituted, external challenges within a specific context provides the opportunity to rethink what ontological security demands. Importantly, this article highlights why a partnership of equals is an urgent imperative for the future of EU-Africa relations, although it remains elusive.